Econometric Estimation Of The Impact Of Oil Prices And Economic Growth On The Diffusion Of Renewable Electricity In Algeria: Using Vecm Model - Tayeb, Saida; Bougueroua, Mariem (جامعة الوادي - University of Eloued, 2021)
The purpose of this article is to investigate the relationship between renewable electricity generation, oil price and economic growth in Algeria using the cointegration approach and Vector Error Correction Model (VECM). We examine simultaneously short-term and long-term impacts between the studies variables: renewable electricity generation, oil price and economic growth during the period 1990–2016. We propose also to forecast the renewable electricity generation to 2025 under different scenarios. The main results of the analysis show that the oil price influenced positively, in the short and long term, the renewable energy generation in Algeria. It implies that higher oil price allows more investment in the renewable energy. This result further confirms the strong dependence of Algerian economy on oil revenues and raises several questions about looking for new sources of financing to develop renewable energies and achieve the sustainable development.
Keywords: Electricity generation, Renewable energy, Oil price, Economic growth, VECM